Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Disiplin Kerja Terhadap Kinerja Karyawan Dinas Tenaga Kerja Kota Semarang - Souisa, Johanis; Dwi Norcahyaningsih; Adhi Widyakto; Aprih Santoso (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to examine and analyze the influence of leadership style, work environment, and work discipline on employee performance at the Semarang City Manpower Office. The population or subject of this study were all employees of the Semarang City Manpower Office. The sampling technique used is a non-probability sampling technique with saturated sampling, because in this study all members of the population can be sampled, namely as many as 90 respondents. This study uses a quantitative method using a questionnaire. Data analysis in this study used the SPSS 24 program which included validity test, reliability test, classical assumption test, multiple regression analysis, hypothesis testing using the t test and R2 test. The results of the analysis in this study indicate that the leadership style (X1) variable has a positive and significant effect on employee performance, the work environment (X2) variable has a positive and significant effect on employee performance, and the work discipline (X3) variable has a positive and significant effect on employee performance. Based on the coefficient of determination 67,8% employee performance can be explained by the independent variables in this study while the remaining 32,2% is influenced by other variables not examined in this study.